Predictors and outcomes of diabetic foot ulcer infection with ESBL-producing bacteria in a large tertiary center. (December 2021) - Leibovitch, Michal; Cahn, Avivit; Gellman, Yechiel N.; Haze, Amir; Peled, Shahar; Amit, Sharon; Elishoov, Ofer; Olshtain-Pops, Karen
Highlights: The prevalence of extended-spectrum beta-lactamase (ESBL)-producing bacteria in patients with diabetic foot infection was 25%. The annual rate of ESBL infection did not change over the years. Patients with ESBL infection had higher SINBAD and Wagner scores upon admission. They were more likely to have been hospitalized in the recent 6 months. Abstract [Au?1]: Objectives: The aim of this study was to describe the predictors and outcomes of infection with extended-spectrum beta-lactamase (ESBL)-producing bacteria in patients with an acute diabetic foot infection (DFI). Methods: The records of patients admitted with acute DFI to a large tertiary hospital during the years 2014–2018 were reviewed. Demographic, clinical, and laboratory data were collected, as well as outcomes regarding amputations and mortality. Only cultures obtained during the first 2 weeks following admission were considered. Results: Cultures were available for 493 patients; 121 (24.5%) included bacteria suspected of being ESBL producers. Patients infected with ESBL-producing bacteria were older, more likely to have peripheral vascular disease (PVD), and had higher SINBAD and Wagner scores upon admission. They were also more likely to have been hospitalized in the recent 6 months. Major amputations were more prevalent in patients with versus without an ESBL-producing bacterial infection (30.6% vs 19.4%; P = 0.010), yet overall amputations and mortality rates were similar. Conclusions: ESBL-producing bacteria are common pathogens in DFI, more prevalent in older patients with PVD, advanced ulcers, and recent hospitalization. They are associated with higher rates of major amputation. These considerations may support the choice of empirical antibiotic therapy in patients admitted with an acute DFI.